THE ROLE OF NOUNS AND THEIR GRAMMATICAL CLASSIFICATIONS (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
This article provides a comprehensive overview of nouns and their grammatical categories, offering insight into how these categories shape sentence structure and meaning. It covers essential concepts such as noun gender, number, case, person, countability, and possessive forms, highlighting their importance in both English and other languages. The article explains how nouns function as the core elements of language, representing people, places, things, and ideas, while also detailing the grammatical rules that govern their usage. By emphasizing the role of nouns in communication, the article illustrates how a deeper understanding of noun categories enhances clarity, precision, and linguistic expression. The final conclusion underscores the necessity of mastering noun categories for effective communication and grammatical accuracy in diverse linguistic contexts.